Profil Suhu, Oksigen Terlarut, dan pH Secara Vertikal Selama 24 Jam di Danau Kelapa Gading Kabupaten Asahan Sumatera Utara - Eva Lia Risky Sinaga; Ahmad Muhtadi; Darma Bakti (Journal Omni-Akuatika, 2016)
Lake Kelapa Gading is an artificial lake located in Asahan district of North Sumatra province. Thepurpose of this study was to determine: 1) description of conditions of temperature, dissolved oxygenand pH vertically in the water for 24 hours, 2) production and consumption of oxygen in the waters ofLake Kelapa Gading. The study was conducted in March-April 2016 with preliminary and mainresearch activities. There are three observation stations are stations 1 (near KJA), station 2 (the areanear the settlement) and station 3 (outlet). The measured temperature ranges from 30-35 ºC.dissolved oxygen highest in the surface waters of 5.12 mg / l during the afternoon and the lowestoccurred at a depth of compensation of 0.64 mg / l when the weather is rainy. The measured pHvalue ranging between 6-9. In general there is a decrease in temperature, dissolved oxygen, and pHwith increasing depth. The highest percent saturation of 71.30 % in the surface waters. Comparisonbetween photosynthesis to respiration indicates that there has been a deficit in respiration is greaterthan the value of photosynthesis. dissolved oxygen concentration has reached a deficit at a depth of36.5 cm to reach at night.  Keywords: dissolved oxygen, lake, pH, saturation, temperature.